2010
DOI: 10.3354/meps08748
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal abundance and egg production rates of Oithona similis and Pseudocalanus elongatus in the northern North Sea: a first comparison of egg-ratio and incubation methods

Abstract: In this study, we examined egg production rates (EPR), clutch sizes, numbers of spawning females and prosome lengths of 2 common marine egg carrying copepods, Oithona similis and Pseudocalanus elongatus, over an annual cycle in the northern North Sea. For both species, we determined EPR using the incubation method, with rates being assessed after 24 (EPR 0 -24 ), 48 (EPR 0 -48 ), and between 24 and 48 h (EPR 24 -48 ) of incubation. For Oithona similis, EPR were also determined by applying the egg-ratio method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…Studies of the egg production of Oithona spp. have described the strong effect of water temperature on hatching times and egg production rates (Sabatini & Kiørboe 1994, Uye & Sano 1995, Drif et al 2010, as has also been documented in calanoid copepods (see Mauchline 1998).Weight-specific egg-production rates reported in the present study for Oithona similis (0.2 to 2% d ; Madsen et al 2008). In general, our maximum weight-specific eggproduction rates are in good agreement with previous studies in high-latitude environments at temperatures similar to ours (Ward & Hirst 2007, Dvoretsky & Dvoretsky 2009b.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Studies of the egg production of Oithona spp. have described the strong effect of water temperature on hatching times and egg production rates (Sabatini & Kiørboe 1994, Uye & Sano 1995, Drif et al 2010, as has also been documented in calanoid copepods (see Mauchline 1998).Weight-specific egg-production rates reported in the present study for Oithona similis (0.2 to 2% d ; Madsen et al 2008). In general, our maximum weight-specific eggproduction rates are in good agreement with previous studies in high-latitude environments at temperatures similar to ours (Ward & Hirst 2007, Dvoretsky & Dvoretsky 2009b.…”
supporting
confidence: 92%
“…Studies of the egg production of Oithona spp. have described the strong effect of water temperature on hatching times and egg production rates (Sabatini & Kiørboe 1994, Uye & Sano 1995, Drif et al 2010, as has also been documented in calanoid copepods (see Mauchline 1998).…”
Section: Egg Production Rates and Efficiencymentioning
confidence: 56%
“…Copepods are one of the most numerous metazoans on the planet; they are ecologically important and play a pivotal role in marine and freshwater biogeochemistry and trophodynamics (Banse, 1995). Reduction in size with increasing temperature, consistent with the TSR (Atkinson, 1994), has been shown in many copepod species, both in controlled laboratory experiments and across seasons in the field (seasonal T-S responses) Drif et al, 2010). Furthermore, the strength of the laboratory T-S response varies widely between species, to the extent that Horne et al (2015) observed an approximate 30-fold difference between the strongest and weakest copepod T-S responses in their dataset on arthropods.…”
Section: Introductionmentioning
confidence: 90%
“…In this study, we investigated transgenerational effects of OA in the calanoid copepod Pseudocalanus acuspes. Copepods of the Pseudocalanus genus are very abundant and widely distributed in temperate, subarctic, and Arctic waters (Aarbakke et al, 2011) and at times they contribute more than one-third of the total zooplankton biomass in the North Atlantic (Head et al, 2003;Thor et al, 2005;Drif et al, 2010). For this study, OA effects on fecundity and metabolism were tested at three different pCO 2 s (400, 900 and 1550 latm) during two generations.…”
Section: Introductionmentioning
confidence: 99%